Materials based on CdS/MgO nanocomposites applied in the photocatalytic hydrogen generation - Angela Gabriela Romero-Villegas; Francisco Tzompantzi; Sandra Ramírez-Rave; Agileo Hernández-Gordillo; Juan Carlos Ruiz; Getsemani Morales-Mendoza; Ricardo Gómez (Journal of Materials Science: Materials in Engineering)
Abstract The synergy between a semiconductor, such as CdS, and an insulator, such as MgO, was approached to improve the photocatalytic H2 evolution. Commercial MgO, nitrate magnesium and carbonate magnesium as Mg precursor of MgO were evaluated in the obtaining of CdS/MgO nanocomposites and their photocatalytic activity. The synthesis of CdS/MgO nanocomposites and its photoactivity as a function of the Mg precursor were sensitive to the MgO structure. A dependence on the mixture of MgO and Mg(OH)2 phases, and the crystallite size in [2 0 0] (D(2 0 0)) and [2 2 0] (D(2 2 0)) crystallographic directions, in the MgO cubic phase, was discovered after X-ray diffraction (XRD) analyses. HR-TEM images revealed the formation of a composite of CdS nanofibres over MgO and their distribution by mapping elemental analysis. Photoactivation was attributed to CdS under blue light, demonstrated by diffuse reflectance spectroscopy (DRS). The photoactivity increased as a function of the MgO support: MgO commercial (~ 3 mmol H2 g −1 CdS h−1) < MgO nitrate (~ 8 mmol H2 g −1 CdS h−1) < MgO carbonate (~ 28 mmol H2 g −1 CdS h−1). The photocatalytic activity as a function of the MgO precursor was correlated with the mixture of MgO/Mg(OH)2 phases as well as the D(2 0 0) and D(2 2 0) crystallite size of the MgO cubic phase.